Depressive-like immobility behavior and genotype × stress interactions in male mice of selected strains. (3rd March 2016) - Chmielarz, Piotr; Kreiner, Grzegorz; Kuśmierczyk, Justyna; Kowalska, Marta; Roman, Adam; Tota, Katarzyna; Nalepa, Irena
Abstract: In this study, we investigated whether basal immobility time of C57BL/6J mice, which are commonly used in transgenesis, interferes with detection of depressive-like behavior in the tail suspension test (TST) after chronic restraint stress (CRS). We included in the study mice of the C57BL/6N strain, not previously compared with C57BL/6J for behavior in the TST, and contrasted both strains with NMRI mice which exhibit low basal immobility. NMRI, C57BL/6J, and C57BL/6N male mice ( n  = 20 per strain) were tested under basal conditions and after CRS (2 h daily for 14 d). NMRI and C57BL/6J mice were differentiated in the TST by low and high basal immobility times, respectively, while the C57BL/6N and NMRI mice showed similar levels of basal immobility. CRSextended the immobility time of NMRI mice in the TST, whereas both C57BL/6J and C57BL/6N mice were unaffected regardless of their initial phenotype. We explored whether detailed analysis of activity microstructure revealed effects of CRS in the TST, which are not apparent in the overall comparison of total immobility time. Interestingly, unlike C57BL/6J and/6N strains which showed no sensitivity to CRS, stressed NRMI mice displayed distinct activity microstructure. In contrast to behavioral differences, all stressed mice showed significant retardation in body weight gain, decreased thymus weight and increased adrenal cortex size. However, after CRS, enlargement of the adrenal medulla was observed in both C57BL/6J and C57BL/6N mice, suggesting similar sympatho-medullary activation and stress coping mechanism in these substrains.